Heart Rate Variability Analysis in Workers Exposed to Methyl Bromide as a Quarantine Treatment. Issue 1 (January 2021) - Choi, Jungmi; Hong, Young-Seoub; Cha, Wonseok; Mo, Hyoung-ho; Park, Min-Goo
Abstract : Objective: To determine whether methyl bromide (MB) fumigation work for plants imported in Korea affects workers' health by assessing heart rate variability (HRV). Methods: We measured HRV indices (TP, VLF, LF, HF, HR, SDNN, pNN50 and HRV-index) and urinary bromide ion (Br − ) in 62 fumigators (study group) and 34 inspectors (the control group) before and after fumigation work. In addition, the relationship between Br − concentration and HRV indices was analysed. Results: The fumigators' post-work HRV indices and Br − level were changed compared with their pre-work values ( P  < 0.001). Conversely, inspectors' values were not shown a difference before and after work. The HRV indices in all subjects were negatively correlated with the Br − levels ( P  < 0.05). Conclusions: Fumigators with high Br − concentrations and low post-work HRV indices following MB fumigation work experienced adverse effects on their autonomic nervous systems. Abstract : Supplemental Digital Content is available in the text